Utilization of Megalithic Sites Vatunonju as Source Study in increase Historical Awareness at Muhammadiyah 1 Palu Vocational School - Putri Ramdhanti; Juraid Abdul Latief; Haliadi Sadi; Iskandar; Misnah (Kirana Publisher (KNPub), 2025)
Problems in study This namely ; (1) How the existence of Megalithic Sites Vatunonju ? (2) How values history of the Megalithic Site Vatunonju ? (3) Why important utilization of Megalithic Sites Vatunonju as source Study in increase awareness History at Muhammadiyah 1 Vocational School, Palu? Research this (1) Describes the existence of Megalithic Sites Vatunonju , (2) Describe values history of Megalithic Sites Vatunonju and (3) Analyzing Megalithic Sites Vatunonju important as source Study in increase awareness history at Muhammadiyah 1 Palu Vocational School. The type of research used is study qualitative with approach descriptive . The data collection technique used researchers namely ; observation , interviews and documents . Then For get processed data with data reduction , data presentation and data verification / conclusions . Research results This show that (1) Megalithic Site Vatunonju located in Vatunonju Village which stores legacy megalithic various prehistoric stone mortar and was first recorded by Dutch missionaries during the colonial period . (2) Values the history contained in Megalithic Sites Vatunonju namely mark education , values culture and beliefs , values knowledge and values history local . (3) Utilization of Megalithic Sites Vatunonju as source Study history proven effective For increase awareness History . Learning at Megalithic Sites Vatunonju who passed through tour education history interesting participants educate For foster a sense of nurturing and inheriting For maintain and preserve legacy inheritance culture ancestors in Central Sulawesi for strengthen awareness history .